Leishmania donovani Utilize Sialic Acids for Binding and Phagocytosis in the Macrophages through Selective Utilization of Siglecs and Impair the Innate Immune Arm. - Saptarshi Roy; Chitra Mandal (Public Library of Science (PLoS), 2016)
BACKGROUND:Leishmania donovani, belonging to a unicellular protozoan parasite, display the differential level of linkage-specific sialic acids on their surface. Sialic acids binding immunoglobulin-like lectins (siglecs) are a class of membrane-bound receptors present in the haematopoetic cell lineages interact with the linkage-specific sialic acids. Here we aimed to explore the utilization of sialic acids by Leishmania donovani for siglec-mediated binding, phagocytosis, modulation of innate immune response and signaling pathways for establishment of successful infection in the host. METHODOLOGY/PRINCIPLE FINDINGS:We have found enhanced binding of high sialic acids containing virulent strains (AG83+Sias) with siglec-1 and siglec-5 present on macrophages compared to sialidase treated AG83+Sias (AG83-Sias) and low sialic acids-containing avirulent strain (UR6) by flow cytometry. This specific receptor-ligand interaction between sialic acids and siglecs were further confirmed by confocal microscopy. Sialic acids-siglec-1-mediated interaction of AG83+Sias with macrophages induced enhanced phagocytosis. Additionally, sialic acids-siglec-5 interaction demonstrated reduced ROS, NO generation and Th2 dominant cytokine response upon infection with AG83+Sias in contrast to AG83-Sias and UR6. Sialic acids-siglecs binding also facilitated multiplication of intracellular amastigotes. Moreover, AG83+Sias induced sialic acids-siglec-5-mediated upregulation of host phosphatase SHP-1. Such sialic acids-siglec interaction was responsible for further downregulation of MAPKs (p38, ERK and JNK) and PI3K/Akt pathways followed by the reduced translocation of p65 subunit of NF-κβ to the nucleus from cytosol in the downstream signaling pathways. This sequence of events was reversed in AG83-Sias and UR6-infected macrophages. Besides, siglec-knockdown macrophages also showed the reversal of AG83+Sias infection-induced effector functions and downstream signaling events. CONCLUSIONS/SIGNIFICANCES:Taken together, this study demonstrated that virulent parasite (AG83+Sias) establish a unique sialic acids-mediated binding and subsequent phagocytosis in the host cell through the selective exploitation of siglec-1. Additionally, sialic acids-siglec-5 interaction altered the downstream signaling pathways which contributed impairment of immune effector functions of macrophages. To the best of our knowledge, this is a comprehensive report describing sialic acids-siglec interactions and their role in facilitating uptake of the virulent parasite within the host.